Implementation of Interactive Artificial Intelligence Voice in Speech Shadowing Method to Improve English Speaking Ability in High School Students: Strategy Analysis and Challenges - Purwo Haryono (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
This study aims to analyze the implementation of Interactive Artificial Intelligence (AI) Voice in the Speech Shadowing method to improve English speaking skills in high school students. The main objectives of this study are to identify implementation strategies, challenges faced, and the effectiveness of using AI Voice in learning to speak English. The method used in this study is a qualitative approach with a multi-site case study type, which was carried out in two A-accredited private schools in Malang City. Data were collected through interviews, observations, and documentation involving teachers and students as key informants. The data analysis technique used is the interactive model of Miles, Huberman, and Saldana, which allows researchers to categorize, organize, and draw conclusions from the data obtained. The results of the study indicate that the integration of AI Voice in the Speech Shadowing method can increase the interactivity of learning and provide direct feedback that accelerates students' mastery of speaking skills. The use of AI Voice allows students to practice with native speakers virtually, which is very effective in improving pronunciation, intonation, and fluency. However, the challenges faced in implementing this technology include limited device infrastructure, curriculum readiness, and student acceptance of new technology. However, overall, the integration of AI Voice has been shown to have a positive impact on improving students' speaking skills. Based on these findings, it is recommended that schools explore the use of technology in language learning in more depth, by providing training to teachers and ensuring the availability of adequate devices. Further research is also needed to examine the potential and challenges of implementing AI Voice in various educational contexts, in order to improve the quality of English learning at a broader level.